Composição da fauna bêntica rasa em duas estações (12 e 25 metros de profundidade) ao longo de um ciclo anual na Baía do Almirantado, Ilha Rei George, Antártica - Echeverría, Carlos Alejandro (2002)
The megafauna, macrofauna and Polychaeta communities at 12 and 25 meters depth in Admiralty Bay (King George Island, Antarctica) were studied along the Antarctic winter (March to December 1999) and summer (December 2000 to March 2001 ), through an entire seazonal cycle. Samplings were carried out using a van-Veen bottom sampler, and were spaced about 15 days to 1 month, resulting in 13 simultaneous samplings in each depth, with 6 replicates each. Communities were significantly (p < 0.05) different between depths along the entire study, although they showed similar faunal compositions. Seasonal variations were not detected along the entire year, suggesting that these communities are not strictly linked with the summer pulse of primary production. Iceberg impacts and water motion caused by storms influenced significantly, although in different ways, the macrofauna and Polychaeta communities at 12 meters. Sediment contents of organic matter increased significantly on summer and declined along winter, reaching its lowest values at the end of this season. This pattern seems closely related with the pattern of macrofauna and Polychaeta diversity along time, and seems to suggest a interdependence between these groups and the sediment organic matter as a possible food source during winter.